(untitled) (Research, Society and Development, 2020)
This work intend to verify the presence of yeast species of the genus Candida associated with the dental prosthesis of patients seen at the clinics of the College of Dentistry of Pernambuco. 34 patients with mobile dental prostheses were selected and, from each patient, a sample of secretion from the surface of the dental prostheses was collected with the aid of a sterile Swab. The identification of Candida species was carried out by conventional methods of colony morphology, germ tube testing, chlamydospore production and biochemical characteristics, such as assimilation and fermentation of carbohydrates and assimilation of nitrogen. Of the samples collected from patients, 61.76% were positive in relation to the presence of yeasts of the genus Candida and 38.24% were negative. Of the positive samples, the species Candida albicans had a higher prevalence with 65.21%; followed by C. dubliniensis with 21.74%. The species C. glabrata, C. apis and C. tropicalis were found in a lower percentage of 4.35%. Thus, concluding that the importance of new studies aiming at the correlation of microbiological findings and clinical manifestations that relate the prevalence of yeasts of the genus Candida in patients with total or partial dental prosthesis is evident.